Adaptation of a Developmental Test to Accommodate Young Children with Low Vision. (March 2017) - Ferreira, Viviana; Albuquerque, Cristina P.
Introduction: This study analyzed the effects of accommodations for children with low vision in the Griffiths Mental Development Scales–Extended Revised (GMDS-ER). Methods: The sample comprised 25 children with low vision and chronological ages between 28 and 76 months. There were two assessment phases: in the first, the Griffiths Scales were administered according to the procedures described in the manual; about two to four weeks later, a second assessment was performed with the same instrument that had been adapted for low vision. Results: The results indicated that there were some favorable differences in the use of item accommodations for children with low vision, including statistically significant improvements of scores in sub-scales A, locomotor; C, language; and E, performance, as well as in the full scale. All children, except one, increased their full scale score; in the subscales, the number of children that increased their scores varied. The combination of different types of accommodations (materials, administration conditions, and success criteria) generated the best results. Still, many children increased their scores with only accommodations to materials (for instance, enhancement of contours and greater visual contrast). Discussion: The results demonstrated the importance of adapting developmental standardized tests for children with low vision. Future studies should increase the sample size and control variables related to type of visual impairment. Implications for practitioners: Test developers and test users should consider accommodations for young children with low vision. That way, the developmental level could be described more precisely and intervention could be better adjusted to each child's abilities. Furthermore, a more accurate developmental assessment of effective child's competencies and difficulties may be useful in terms of eligibility criteria for special education services.